Apollo and Comet Media Design to Practice Science Literacy for Elementary School Students - Nur Azizah; Suryanti Suryanti; Nadi Suprapto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Science literacy is very important to be mastered by students. In the literacy process, students need learning media that are in accordance with the characteristics of students and materials. Media design is based on a game design framework, namely empathic or analytical (emphatic), defining (define), developing ideas (ideate), making prototypes (prototyping), and testing (playtest). The stages of the game design framework are in line with the steps for selecting learning media, namely ASSURE. The design of Apollo and Comet media that is in accordance with these stages can produce media games that are not only able to entertain children, but also facilitate students to train their literacy skills. This research used a nonequivalent pretest posttest control group research design used for Quasi Experimental Design. Data on increasing scientific literacy was obtained by giving a pretest and posttest using a scientific literacy test sheet by adapting the PISA test.. Students' scientific literacy increased by 74.8562 with a high category based on the results of the N-Gain.